Comparison between line and surface mesh models to represent the rotator cuff muscle geometry in musculoskeletal models - Hoffmann, M.; Haering, D.; Begon, M. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Accurate muscle geometry (muscle length and moment arm) is required to estimate muscle function when using musculoskeletal modelling. In shoulder, muscles are often modelled as a collection of independent line segments, leading to non-physiological muscles trajectory, especially for the rotator cuff muscles. To prevent this, a surface mesh model was developed and validated against 7 MRI positions in one participant. Mean moment arm errors was 11.4% for the line vs. 8.8% for the mesh model. While the model with independent lines led to some non-physiological trajectories, the mesh model gave lower misestimations of muscle lengths and moment arms.